Embracing the Chaotic: Cynefin and Humanitarian Response - Morealtitude (2010)
Note: Many thanks to Dave Snowden for his willingness to comment on th is article prior to release Because I’m always a little behind the eig ht-ball, a friend of mine* recently introduced me to the …